Teaching and classroom management strategies of Indonesian master teachers: investigating a vocational English classroom - Rido, Akhyar; Radha M.K. Nambiar,; Noraini Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2016)
government in effectively attending to the needs of the global workforce that demands young and skilled human capital. In the process, they are expected to demonstrate effective pedagogical practices. This study examines the teaching and classroom management strategies of Indonesian vocational English master teachers and the effects on the students. Using a qualitative approach, this study involved three selected master teachers. Data were collected through 18 sessions of observations, 45 hours of video-recordings, and interviews with 34 students. The results demonstrated that, in terms of teaching strategies, the master teachers used a wide variety of teaching techniques, focused on speaking skills, and combined various teaching sources and aids. In terms of classroom management strategies, they facilitated group work, organised seating arrangement in a traditional way, and emphasised classroom discipline. The strategies used by the MTs were also positively perceived by the students as they had a better understanding of the lesson, an enjoyable learning experience, improved their speaking skills, shared knowledge with their friends, and enjoyed better mutual respect. The findings of this study can be used by stakeholders as a platform to enhance learning of English language in the vocational context in Indonesia.